Aspectos clínico-epidemiológicos e distribuição espacial da Hanseníase em menores de 15 anos no Estado do Maranhão - MOREIRA, Rodolfo José de Oliveira (2023)
Leprosy is an infectious disease that evolves slowly and progressively. Its occurrence in children under 15 years of age indicates early exposure to the etiological agent in the child's living environment, in addition to suggesting high numbers of cases of the disease and active transmission. The objective was to analyze the clinical-epidemiological aspects and the spatial distribution of leprosy in children under 15 years of age in the state of Maranhão. This is an ecological study with different analysis measures using secondary data from compulsory notifications available at the State Coordination of the Leprosy Program in the period from 2010 to 2021. New cases of leprosy in children under 15 years of age were included by municipality of residence from the state of Maranhão. Descriptive statistics were performed, thus tracing the clinical-epidemiological profile of leprosy in children under 15 years of age in the state. Incidence rates were estimated for each year and by Regional Health Unit (URS) in Maranhão and also for the state, and subsequently the trend analysis of the indicator was carried out using Prais-Winsten regression. To identify the factors associated with the multibacillary (MB) operational classification, univariate and multivariate logistic regression models and odds ratios were used, considering a 5% significance level. To perform the area analysis, the incidence rates were divided into 3 four-year periods (2010 to 1013; 2014 to 2017; 2018 to 2021) through cumulative incidence, distributed and spatially represented on maps. To perform the spatial analysis of the data, the Global Moran Global and Local Moran Index (LISA) was used. A total of 3,834 new cases of leprosy in children under 15 years of age were analyzed. As for the clinical-epidemiological profile, the variables male gender (54.02%), age 10 to 14 years (63.82%), brown race (69.54%), living in an urban area (72.93% ), operational class in the MB diagnosis (56.60%), having 1 to 5 registered contacts (70.76%), having examined 1 to 5 contacts (67.01%), having 1 to 5 lesions (68 .21%), no reactional episode (71.94%), grade 0 neural impairment at diagnosis (73.40%), no affected nerve at diagnosis (56.60%) and discharge as type of output (84. 74%) stood out as the majority of cases. The tendency of the incidence of the annual detection coefficient was decreasing in the state of Maranhão and in 8 URS, remaining stable in the others. The factors associated with the MB operational classification were: age between 10 and 14 years, male gender, residing in a non-urban area, having had a reactional episode and having physical disability. The spatial analysis showed positive spatial autocorrelation by the Global Moran Index in the 3 quadrenniums and LISA showed significance and cluster municipalities in the 3 quadrennia. The study showed that the incidence of new cases was decreasing in eight regions of the State and stable in the others. Factors associated with the MB operational classification in children under 15 years old are 10 to 14 years old, male, living in a non-urban area, having had a reactional episode and presenting physical disability, and that there is a positive autocorrelation between the annual detection coefficient and the presence of clusters in the state.